Impact of rAAV-shRNA treatment targeting mechanosensitive Ilk1 and Fermt2 in a mouse model of sepsis-induced muscle weakness - Alexander Pacolet; Inge Derese; Lies Pauwels; Sarah Vander Perre; Maxime Smits; Chris Van den Haute; Sarah Derde; Katrien Koppo; Rik Gijsbers; Lies Langouche (PLoS ONE, 2025)
Introduction Intensive-care-unit-acquired-muscle-weakness is a debilitating complication of sepsis, characterized by loss of muscle mass and functionality. Immobilization is an important trigger, but the role of disturbed mechanical signaling is incompletely understood. In health, the integrin-receptor-complex with key components Kindlin2 (KIND2/ Fermt2 ) and integrin-linked-kinase (ILK/ Ilk1 ) converses mechanical forces into biochemical signals to regulate muscle mass. We hypothesize that this complex, through key elements KIND2 and ILK, plays a role in sepsis-induced-muscle-weakness. Methods AAV2/9-vectors expressing shRNA-sequences against Ilk1, Fermt2 or noncoding-control-gene were injected in tibialis anterior (TA) muscles of 24w-old male C57BL/6J mice. Two-weeks-post-injection, after knockdown validation, mice were made septic by cecal ligation and puncture. Five-days-post-sepsis muscle force, mass and fiber size were quantified and expression of mechanosensitive elements and downstream pathways of the integrin-receptor-complex was assessed. Results Two-weeks-post-injection the respective sh-targets were strongly suppressed (mRNA Ilk1 –44%, Fermt2 –76%, protein ILK −34%, KIND2–70%). In rAAV-sh- controls , sepsis induced upregulation across TA and EDL muscle of Ilk1 and Fermt2 and integrin-receptor-complex-related genes Itga 7, ItgB1 , Tln1 , Lims1, Lims2, Parva ( P < 0.001 ), whereas in SOL muscle Lims1, Lims2 and Fermt2 were not and Vcl1 ( P < 0.001 ) was upregulated. In TA and EDL, but not in SOL, rAAV-sh Ilk1 and rAAV-sh Fermt2 attenuated upregulation of respective targets down to healthy controls, but without affecting expression of other integrin-receptor-complex-related genes. TA muscle force or weight were not affected by rAAV-sh Ilk1 or rAAV-sh Fermt2 ( P > 0.05 ), whereas muscle fiber size reduction (−20.7% in Sepsis shControl) was attenuated up to −13.4% (Sepsis sh Ilk1 , P < 0.001 ) and −12.3% (Sepsis sh Fermt2 , P < 0.001 ). Sepsis or sh-treatment did not shift TA fiber types. Expression of markers of atrophy, inflammation, autophagy, protein synthesis and regeneration were affected by sepsis, but not by sh-treatment. Only markers of metabolism Slc2a4 ( P < 0.05) and Rac1 ( P < 0.01 ) were further affected by sh-treatment. Conclusions Sepsis induced upregulation of integrin-receptor-complex-related genes but attenuating the upregulation of Ilk1 or Fermt2 did not affect the development of muscle weakness, although muscle fiber size was better preserved, arguing against a key role for Ilk1 or Fermt2 .